Tardy ulnar nerve palsy after fracture non-union medial epicondyle of humerus – An unusual case - Thiyam, Rajesh (J Clin Orthop Trauma, 2015)
Tardy ulnar nerve palsy is a chronic clinical condition characterised by delayed onset ulnar neuropathy. Typically tardy ulnar nerve palsy occurs as a consequence of non-union of lateral condyle in child resulting in cubitus valgus deformity which ultimately is the cause of ulnar nerve palsy. However very few literature are available for tardy ulnar nerve palsy as a result of old fracture of medial epicondyle without cubitus varus or valgus deformity. We report a rare case of tardy ulnar nerve in an adult male with fracture non-union of medial epicondyle of humerus.